Human Resource Development in China: The Triple Helix Model for Global Tech Expansion - Andika Drajat Murdani; Hasna Wijayati; Halifa Haqqi (Penerbit Goodwood, 2026)
Purpose: Rapid technological competition has elevated human resource development as a strategic priority, particularly for countries seeking to expand their global technological influence. This study examines how human resource development strategy in China supporting global technological expansion. Research Methodology: This study employs a qualitative descriptive approach using a systematic literature review of academic publications, national policy documents, and official reports on education, innovation, and workforce development in China. The data drawn from peer-reviewed journals, government publications, and international organization reports, were analyzed through thematic analysis to identify key patterns and strategic mechanisms shaping China’s HRD model. Results: China’s strategy is built on the Triple Helix model, operationalized through three interrelated mechanisms: (1) education and research institutions as strategic HRD infrastructure, supported by expanded higher education and sustained R&D investment; (2) university-industry collaboration as an institutionalized talent pipeline that reduces skill mismatches and enhances workforce readiness; and (3) strong state coordination that integrates education policy, innovation strategy, and industrial development into a coherent macro-level HRM architecture. Conclusions: Triple Helix Model represents a state-enhanced approach to human resource development which education systems deliberately mobilized to sustain long-term technological competitiveness. Limitations: This study relies exclusively on secondary data and literature-based analysis. Contributions: Contributes to Strategic and International HRM by offering a macro-level perspective on how education systems can function as strategic HRM mechanisms within national innovation frameworks, providing insights for policymakers and HRM scholars responding to global technological change.